ANALISIS PENGARUH INFLASI DAN TINGKAT SUKU BUNGA SBI TERHADAP OBLIGASI SYARIAH MUDHARABAH DAN IJARAH DI INDONESIA - Yuliana, Indah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2008)
In some recent years, Islamic financial and economy grows rapidly. This evidence can be proved by the growth of Syariah Financial Institution (LKS) in Indonesia that reached to 70 % . This phenomena was contradictory to Conventional Financial Institution that reached only one digit rate of average growth. One of the booming instruments in Islamic financial is syariah obligation. In general, this obligation which is offered by Emiten over subscribe. It become the alternative source of funds while the investors already sick and tired with the conventional financial portfolio products. Activities in capital market influenced by macro economy condition in a country. If the macro indicator stable, capital market activities would be stimulate. There are many indicators of macro economy used for calculate the national growth, such as the inflation and interest rate level. The purpose of this research is to knowing how the inflation and SB! interest rate level influences the syariah obligation return Mudharabah and Ijarah in Indonesia simultaneously. Population in this research is syariah obligation return Mudharabah and ljarah level in Indonesia. The instrument used in this analysis is double linear regression. The results of this research are (1)Both inflation and SBI interest rate level significantly influences syariah obligation return Mudharabah (2) Both inflation and SBI interest rate level were not significantly influences syariah obligation return Ijarah.